Avaliação da molhabilidade de soluções de tensoativos em aço inoxidável - Nascimento, André Ezequiel Gomes do (2009)
With the increasing industrialization of the planet caused by globalization, it has become increasingly common to search for highly resistant and durable materials for many diverse branches of activities. Thus, production and demand for materials that meet these requirements have constantly increased with time. In view of this, stainless steel is presented as one of the materials which are suitable applications, due to many features that are interesting for several segments of the industry. Concerns of oil companies over heavy oil reservoirs have grown steadily for the last decades. Rheological properties of these oils impair their transport in conventional flow systems. This problem has created the need to develop technologies to improve flow and transport, reducing operation costs so as to enable oil production in the reservoir. Therefore, surfactant-based chemical systems are proposed to optimize transport conditions, effected by reduction of interfacial tensions, thereby enhancing the flow of oil in ducts and reducing load losses by friction. In order to examine such interactions, a study on the wettability of metallic surfaces has been undertaken, represented by measuring of contact angle of surfactant solutions onto flat plates of 304 stainless steel. Aqueous solutions of KCl, surfactants and mixtures of surfactants, with linear and aromatic hydrocarbon chain and ethoxylation degrees ranging between 20 to 100, have been tested. The wettability was assessed by means of a DSA 100 krüss goniometer. The influence of roughness on the wettability was also investigated by machining and polished the stainless steel plates with sandpapers of references ranging between 100 of 1200. The results showed that sanding and polishing plates result in decrease of wettability. As for the solutions, they have provided better wettability of the stainless steel than the KCl solutions tested. It was also been concluded that surfactant mixtures is an option to be considered, since they promote interactions that generate satisfactory contact angles for a good wettability on the stainless steel plate. Another conclusion refers to the influence of the ethoxylation degree of the nonionic surfactant molecules on wettability. It has been observed that contact angles decrease with decreasing ethoxylation degrees. This leads us to conclude that molecules with higher ethoxylation degree, being more hydrophobic, decrease the interaction of water with the ducts, thereby reducing friction and improving the flow